THE CHEMISTRY OF MATERIALS FOR FACE MASKS: DEVELOPING EFFECTIVE FILTERS AGAINST COVID-19 (International Seven Journal of Multidisciplinary, 2022)
The COVID-19 pandemic highlighted the urgent need for effective personal protective equipment, particularly face masks capable of filtering viral particles. This article explores the role of chemistry in developing advanced filtration materials, focusing on polymer science, electrostatic charging, nanotechnology, and antimicrobial surface treatments. Materials such as melt-blown polypropylene, electrospun nanofibers, and biodegradable polymers have been engineered to maximize filtration efficiency while maintaining breathability and comfort. Additional innovations include hydrophobic coatings, smart sensing elements, and antiviral nanomaterials such as graphene derivatives. The study underscores the multidisciplinary advances in material chemistry that have enabled rapid and scalable mask production to address both health and environmental challenges.